PROSES RESELIENSI WARIA TERHADAP PENOLAKAN LINGKUNGAN DI DESA LUMPATAN KEC. SEKAYU KABUPATEN MUSI BANYUASIN (PENDEKATAN FENOMENOLOGI) - Mulia Marita Lasutri Tama; Mazidawati Mazidawati (Media Bina Ilmiah, 2023)
This study aims to determine the process of resilience in transgender women when they experience rejection from their environment and what factors affect the resilience process in transgender people. There were 2 research subjects with waria characteristics who already had resilience traits. This study uses a qualitative method with a phenomenological approach. The results showed that the two subjects had different levels of resilience in the two subjects. Subject Y is currently at the thriving resilience level stage (developing rapidly). While subject H in the resilience process is in the recovery stage. Resilience in subject Y is more influenced by factors of emotion regulation and impulse control. Whereas in subject H, of all the factors that are more dominant or much influenced by high optimism for his life. So it can be concluded that there are differences in the level of resilience and resilience factors in the process of resilience in both subjects.